“History of Ukrainian Сulture” as a research field and academic discipline: suggestions for solving pressing problems - Dovga, Larysa; Lihus, Mariia (Filosofiya osvity. Philosophy of Education, 2023)
The article reconsiders the teaching and learning of the academic discipline “History of Ukrainian Culture”. This course is justified as fundamental in teaching humanities and the key to the success of modern democracies. It is noted that the teaching of the discipline “History of Ukrainian Culture” in Ukrainian higher education institutions is currently based mainly on the history of artistic culture, neglecting the fact that the history of national culture is a philosophical discipline which apart from artistic culture examines the cultural worldview, value system, and political and economic state models. Therefore, a philosophical justification of the “History of Ukrainian culture” as a research field and educational discipline is suggested. In particular, the historical-philosophical methodology of Gorsky is applied, from the standpoint of which the concept of national culture is conceptualized as a multidimensional field of cultural creativity, where the national idea is discussed and formulated through the personal character of every cultural-historical epoch’s worldview. The authors address Hofstede’s sociological approach to measuring value frameworks of national cultures and justify the reasonability to interpret the history of Ukrainian culture as a performative practice of curating the past, conveying cultural values, cultural criticism, and composing the shared knowledge in the context of public construction of the Ukrainian modern national identity. It is concluded that the suggested perspective on theoretical conceptualization and practical implementation of the academic discipline “History of Ukrainian Culture” may encourage students to research the national past, construct a positive national-cultural identity, and expertly represent Ukrainian culture on the world stage.